Exposure–efficacy Relationships for Vedolizumab Induction Therapy in Patients with Ulcerative Colitis or Crohn's Disease. (17th February 2017) - Rosario, Maria; French, Jonathan L; Dirks, Nathanael L; Sankoh, Serap; Parikh, Asit; Yang, Huyuan; Danese, Silvio; Colombel, Jean-Frédéric; Smyth, Michael; Sandborn, William J; Feagan, Brian G; Reinisch, Walter; et al.
Abstract: Background and Aims: A positive relationship between vedolizumab trough serum concentrations and clinical outcomes in patients with ulcerative colitis [UC] or Crohn's disease [CD] has been reported. Here we further explore exposure–efficacy relationships for vedolizumab induction therapy in post hoc analyses of GEMINI study data. Methods: Vedolizumab trough concentrations at Week 6 or 10 were grouped in quartiles and clinical outcome rates calculated. Exposure–efficacy relationships at Week 6 and potential baseline covariate effects were explored using logistic regression and individual predicted cumulative average concentration through Week 6 [Caverage ] as exposure measure. Results: Higher vedolizumab concentrations were associated with higher clinical remission rates; the exposure–efficacy relationship was steeper for UC than CD. Unadjusted analyses overestimated the relationship, more so for CD. From covariate-adjusted models, average probability of remission at Week 6 increased by approximately 15% for UC and 10% for CD between Caverage values of 35 and 84 µg/ml [5th and 95th percentiles, respectively]. On average, patients with higher albumin, lower faecal calprotectin [UC only], lower C-reactive protein [CD only], and no previous tumour necrosis factor-α [TNFα] antagonist use had a higher remission probability. Previous TNFα antagonist use had the greatest impact; remission probability was approximately 10% higher in treatment-naïve patients. Conclusions: Higher vedolizumab serum concentrations were associated with higher remission rates after induction therapy in patients with moderately to severely active UC or CD. This relationship is affected by several factors, including previous TNFα antagonist use. Prospective studies are needed to assess vedolizumab dose individualisation and optimisation.